2012
DOI: 10.2118/139766-pa
|View full text |Cite
|
Sign up to set email alerts
|

Casing Burst Stresses in Particulate-Filled Annuli: Where Is the Cement?

Abstract: Summary For burst design, engineers routinely assume that the casing annular space is filled by a fluid equivalent. This assumption ignores mechanical resistance provided by solid cement. Some studies addressed this shortcoming by modeling the cement sheath as a solid with elastic failure criteria. Prior work used cement elastic modulus and Poisson's ratio to classify cement as "ductile" (soft) or "brittle" (hard). In the current study, numerical results from finite-element analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…By comparison, preliminary calculations using Barlow's formula for the expansion of a cylindrical metal tube [7,124], plus typical casing tube dimensions and plastic yield data for conventional casing steels [56], suggest that expanding conventional wellbore casing via internal pressurisation would require effective internal stresses in the range of 100-300 MPa. Constraints from casing burst studies provide similar values [39,64]. As such, the stresses that could potentially be induced, if a wellbore would be plugged with low-porosity CaO aggregate, are more than sufficient to bring about casing expansion leading to mechanical closure of annuli and fractures similar to that seen in the experiments of Kupresan et al [74,75].…”
Section: Introductionsupporting
confidence: 56%
“…By comparison, preliminary calculations using Barlow's formula for the expansion of a cylindrical metal tube [7,124], plus typical casing tube dimensions and plastic yield data for conventional casing steels [56], suggest that expanding conventional wellbore casing via internal pressurisation would require effective internal stresses in the range of 100-300 MPa. Constraints from casing burst studies provide similar values [39,64]. As such, the stresses that could potentially be induced, if a wellbore would be plugged with low-porosity CaO aggregate, are more than sufficient to bring about casing expansion leading to mechanical closure of annuli and fractures similar to that seen in the experiments of Kupresan et al [74,75].…”
Section: Introductionsupporting
confidence: 56%
“…As a result, both active and passive loading evolved on the casing, which exacerbate thermally induced strain based cyclic axial loading occurring in conjunction with net internal or external pressure differentials. Kalil and McSpadden (2012) study on casing burst stress in particulate annuli concluded that depending on the casing grade bonded annulus fill material provides more than 5% added support to the cemented casing's nominal burst rating.…”
Section: Collapse/burst Failurementioning
confidence: 99%
“…Pollock, R. et al [ 17 ] emphasized the need for the improvement of cement in thermal stimulation wells due to excessive cement failures under extreme temperature conditions. Kalil, I. et al [ 18 ] used finite element analysis to investigate the casing burst effect when cement is present in the sheath. This was performed to overcome the limitations of previous models that assume that the casing annular space is filled by a fluid equivalent instead of cement.…”
Section: Introductionmentioning
confidence: 99%